Competency Development of Early Childhood Educators through Social Emotional Learning Program to Prevent Bullying Behavior - Ramadan, Mariana Panji; Dhieni, Nurbiana; Hartati, Sofia (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2025)
Bullying is a social problem that can occur starting from childhood, and not only occurs in the social environment where people live but also includes the school environment including in Early Childhood Education units. Bullying is a condition when children are faced with negative actions carried out by individuals or groups with frequent frequency and considerable intensity. Bullying in the school environment as a form of one of the aggressive behaviors carried out repeatedly by individuals or groups who feel they have power over other individuals who are considered weaker. Bullying behavior is related to the lack of social emotional skills possessed by children. The research has implications for interventions or prevention that seek to focus on social emotional skills, which can be a factor in maintaining relationships so that no child is victimized, as it is associated with significant behaviors among children who are bullies in peer friendships. Cruel treatment of others. Educators in ECD settings can assist young children in developing important social-emotional skills that can be used to prevent bullying behavior. These activities include teaching children to empathize with the feelings of others, differentiate between their own and others' emotions, take on new roles, and become more emotionally responsive.